Effects of Obesity on the Perioperative Results and Continence Status in Laparoscopic Radical Prostatectomy - Onur Kaygısız; Çağdaş Gökhun Özmerdiven; Berna Aytaç Vuruşkan; Burhan Coşkun; Kadir Ömür Günseren; Yakup Kordan; İsmet Yavaşçaoğlu; Hakan Vuruşkan (Galenos Yayinevi, 2017)
Objective: To assess the effects of obesity on the surgical success and perioperative results and continence status in laparoscopic radical prostatectomy (LRP). Materials and Methods: The results of 300 consecutive patients undergoing LRP between April 2004 and January 2014 were analyzed retrospectively. Twenty patients were excluded from the study, thus, 280 patients remained. The patients were separated into 3 groups according to their body mass index. Based on this classification, group 1 (<25 kg/m2) was normal, group 2 (25-30 kg/m2) was overweight, and group 3 (>30 kg/m2) was obese. The demographic data, intraoperative results, pathological results, and states of continence were compared among the groups. Results: There were 81 patients in group 1, 152 patients in group 2, and 47 patients in group 3. There were no significant differences when the groups were compared according to age and prostate specific antigen values. The intraoperative blood loss was high in group 3 only. Moreover, the estimated blood loss, transfusion, operative time, bilateral nerve-sparing rate, hospitalization days, and complication rate were similar between the groups. There were no significant differences when the pathological results were compared according to the positive surgical margins and Gleason scores. Although the continence rates in group 3 were significantly low 6 months after the operation (p<0.05), the results were similar at 1 year (p=0.738). Conclusion: LRP can be applied confidently in obese patients as well as normal and overweight patients.